Science Diplomacy in Latin America and the Caribbean: Current Landscape, Challenges, and Future Perspectives - Soler, Marga Gual (Frontiers in Research Metrics and Analytics, 2021)
Science, technology, and innovation are taking center stage in international affairs and increasingly influencing the geopolitical dynamics and a country's standing on the global stage. New scientific and technological advancements are acquiring greater strategic relevance to ensure competitive advantages in the twenty-first century global order. At the same time, international scientific collaboration contributes to generating and democratizing knowledge and improving relations between countries as a “soft power” tool to coordinate science-based solutions to transboundary problems, and to build bridges between countries with tense diplomatic relations. Science diplomacy is not a new concept, but most of its intellectual foundations and practical applications have emerged in the Global North. This article describes the diverse approaches, policies and practices adopted by Latin American and Caribbean countries at the national, sub-national, and regional levels. It analyzes their successes and challenges and identifies opportunities to guide the region toward a common science diplomacy strategy to achieve sustainable development through incorporating science as a permanent element in the foreign policy toolkit of Latin American nations. By documenting and illuminating best practices in the region, this article also seeks to balance the emphasis that has so far been largely concentrated on the regions of Europe and North America and contribute to future efforts and strategies for the development of sustainable science diplomacy mechanisms at the national, regional, North-South and South-South levels.